2021
DOI: 10.1002/cjoc.202100539
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization of Rare‐Earth Metal Chlorides Bearing Indolyl‐Based NCN Pincer Ligand and Their Catalytic Activity toward 1,4‐cis Polymerization of Isoprene

Abstract: Main observation and conclusion A novel indolyl‐based NCN pincer ligand precursor HL (HL = (1‐(2‐(CH2)4NCH2CH2)‐3‐(2,6‐iPr2C6H3N=CH)C8H5N)) was rationally and precisely designed, and successfully prepared in a high yield. Lithiation of HL with nBuLi in n‐hexane, followed by treatment with RECl3 in THF led to the isolation of rare‐earth metal chlorides in monomeric form (κ3‐L)RECl2(THF) (RE = Sc(2), Yb(3)), and dimeric form [(κ3‐L)RECl(THF)(μ‐Cl)]2 (RE = Er(4), Y(5)) bearing the novel indolyl‐based NCN pincer l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 85 publications
4
17
0
Order By: Relevance
“…Previous reports have indicated that higher concentrations of IP can lead to a preference for cis -1,4, which explains the higher cis -1,4 selectivity at shorter reaction times. 28 It is interesting that the longer reaction time with 8 ( Table 1 , entry 3) has no presence of cis -1,4 selectivity, while the shorter time has 8% cis -1,4 selectivity ( Table 1 , entry 6). Since cis -1,4 selectivity seems to drop with IP concentration, this could be due to the cis -1,4 getting buried in the baseline of the NMR spectrum for the long reaction times.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports have indicated that higher concentrations of IP can lead to a preference for cis -1,4, which explains the higher cis -1,4 selectivity at shorter reaction times. 28 It is interesting that the longer reaction time with 8 ( Table 1 , entry 3) has no presence of cis -1,4 selectivity, while the shorter time has 8% cis -1,4 selectivity ( Table 1 , entry 6). Since cis -1,4 selectivity seems to drop with IP concentration, this could be due to the cis -1,4 getting buried in the baseline of the NMR spectrum for the long reaction times.…”
Section: Resultsmentioning
confidence: 99%
“…We had found that the (3-imino)­indole 1-(2′-(CH 2 ) 4 NCH 2 CH 2 )-3-(2′,6′-Pr i 2 C 6 H 3 NCH)­C 8 H 5 N) can be deprotonated by Bu n Li to form the ((3-imino)­indol-2-yl)lithium salt 2-Li-1-(2′-(CH 2 ) 4 NCH 2 CH 2 )-3-(2′,6′-Pr i 2 C 6 H 3 NCH)­C 8 H 5 N) . This lithium salt can perform salt elimination reactions with lanthanide halides to yield (3-imino)­indol-2-yl lanthanide complexes .…”
Section: Resultsmentioning
confidence: 99%
“…(3-Imino)­indol-2-yl anions can be viewed as derivatives of the 4-alkenyl anions of but-2-en-1-imines. In recent years, some of us (Wang and Zhou) have found that these types of anions are useful C , N -chelating ligands for the preparation of lanthanide complexes that show high catalytic activity in isoprene polymerization. Noting that transition-metal complexes of (3-imino)­indol-2-yl ligands are scarce, , we then initiated a study on 3d metal complexes of (3-imino)­indol-2-yl ligands. Herein, we wish to report the synthesis, characterization, and redox properties of iron complexes bearing (3-imino)­indol-2-yl ligands, which revealed that this type of C , N -chelating ligand is redox noninnocent.…”
Section: Introductionmentioning
confidence: 99%
“…[ 13 ] Since then, various catalysts including metallocene catalysts, [ 13‐18 ] half‐metallocene catalysts, cyclopentadienyl (Cp)‐free group 4 metal catalysts, late transition metal catalysts, and more recently cationic rare earth metal half‐sandwich alkyls have been reported to catalyze copolymerization of ethylene and NBE and other cyclic olefin monomers (Scheme 1). [ 19‐29 ] The resulting COCs with promising physical properties have also attracted extensive attention in both industrial and academic communities. [ 30‐43 ] Mitsui and Polyplastics have launched their commercial COCs: APEL® and TOPAS®, respectively.…”
Section: Background and Originality Contentmentioning
confidence: 99%